2013
DOI: 10.1111/vru.12123
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Imaging Findings Associated With Lateral Cerebral Ventriculomegaly in English Bulldogs

Abstract: Multiple congenital or developmental anomalies associated with the central nervous system have been reported in English Bulldogs. The purpose of this retrospective study was to identify and describe the prevalence and MRI characteristics of these anomalies and their association with presence and degree of cerebral ventriculomegaly. Magnetic resonance imaging studies of 50 English Bulldogs were evaluated. Forty-eight dogs had some degree of cerebral ventriculomegaly, 27 of which had an otherwise normal brain. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 10 publications
(32 reference statements)
0
19
0
1
Order By: Relevance
“…Abnormalities included cranial vault fractures, facial bone fractures, regional brain hypodensity consistent with edema, areas of brain hyperdensity consistent with hemorrhage, and a mass effect, as represented by midline shift or ventricular asymmetry. Hydrocephalus, which was detected in 7 dogs, can be an incidental finding [21][22][23][24] and therefore did not necessarily represent brain injury.…”
Section: Discussionmentioning
confidence: 99%
“…Abnormalities included cranial vault fractures, facial bone fractures, regional brain hypodensity consistent with edema, areas of brain hyperdensity consistent with hemorrhage, and a mass effect, as represented by midline shift or ventricular asymmetry. Hydrocephalus, which was detected in 7 dogs, can be an incidental finding [21][22][23][24] and therefore did not necessarily represent brain injury.…”
Section: Discussionmentioning
confidence: 99%
“…However, most of the reported literature focuses on using MRI retrospectively for diagnostic or veterinary applications and not that of an active tool for drug discovery. Of the published literature for dog brain ventricles, many have investigated the ventricles under suspicion or with known pre-existing conditions or disease states (Bentley, et al, 2013;Driver, Rusbridge, Cross, McGonnell, & Volk, 2010;Pivetta, De Risio, Newton, & Dennis, 2013;Ryan, Glass, Seiler, Zwingenberger, & Mai, 2013). Only select studies have evaluated all four ventricles (Driver, et al, 2010) while others reported lateral ventricle volumes only (Cardoso, Lachat, Lopes, Santos, & Colli, 2011;Kii, et al, 1998;Kii, et al, 1997;Su, et al, 2005).…”
Section: Accepted Manuscriptmentioning
confidence: 98%
“…Only select studies have evaluated all four ventricles (Driver, et al, 2010) while others reported lateral ventricle volumes only (Cardoso, Lachat, Lopes, Santos, & Colli, 2011;Kii, et al, 1998;Kii, et al, 1997;Su, et al, 2005). Additionally, previous quantitative work has often calculated ventricular area, rather than volume (Esteve-Ratsch, Kneissl, & Gabler, 2001) or used non-Beagle dog breeds, which are the most commonly used model for pharmaceutical use (Driver, et al, 2010;Ryan, et al, 2013;Vite, Insko, Schotland, Panckeri, & Hendricks, 1997). For the purposes of drug discovery, ventricle volumes, rather than area, may be more accurate due to increased sampling of the entire ventricle system, and the inclusion of the third and fourth ventricles in assessment may further identify potentially subtle changes in drug effects.…”
Section: Accepted Manuscriptmentioning
confidence: 98%
“…Although ventricular size varies among dog breeds, the diagnosis of hydrocephalus is usually made when there is excessive enlargement of the ventricular system . If a focal portion of the ventricular system is dilated, obstructive hydrocephalus should be suspected.…”
mentioning
confidence: 99%
“…2 A third classification of enlargement of the ventricular system, hydrocephalus ex vacuo or compensatory hydrocephalus, occurs as a consequence of loss of neuroparenchyma. 3 Although ventricular size varies among dog breeds, [4][5][6][7][8] the diagnosis of hydrocephalus is usually made when there is excessive enlargement of the ventricular system. 9 If a focal portion of the ventricular system is dilated, obstructive hydrocephalus should be suspected.…”
mentioning
confidence: 99%